A tale of two cities : macroeconomic differences between Hong Kong and Singapore. - Fong, Choi Foong. (2008)
Besides the exchange-rate regimes, this report seeks to establish the point that wage flexibility and rise of China have also influence the macroeconomic performances of Hong Kong and Singapore. In addition, the possible evolutions of Hong Kong Exchange-Rate regimes are looked into too.